Motion of energy - Trivedi, Nripesh (International Journal of Scientific Research and Management (IJSRM), 2023)
In [1], it was given that the principle defining movement of energy is equilibrium. This paper describes a further notion or reason that defines movement of energy. In [2], it was stated that energy moves from a place of higher magnitude to a place of lower magnitude. This paper highlights a simple reason defining motion of energy by reasoning.